FIXED POINT THEOREMS IN SYMMETRIC 2-CONE BANACH SPACE (_p, \|·\|^c_p) - Sahiner, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
The present article is concerned with lp sequences spaces in point of its symmetric 2-cone norm structure. Further, fixed point theorem for this space is proved.